Effectiveness and kinematic analysis of initial step patterns for multidirectional acceleration in team and racquet sports - Vuong, J.-L.; Edel, A.; Voß, P.; Ferrauti, A. (Journal of Human Kinetics, 2022)
The ability for quick multidirectional accelerations is crucial for athletic performance in team and racquet sports. So far, there has been little research dedicated to different initial step patterns usually applied by players. Therefore, the present study investigated the kinematic characteristics and effectiveness of the following step patterns: Jab Step (JS), Pivot Step (PS), Gravity Step (GS) and Counter Step (CS). Twenty-two male competitive team and racquet sport athletes completed maximum lateral accelerations utilizing the step patterns. Following familiarization with each step pattern, three 5 m sprints (5 m STs) into both directions (left & right) were completed. Sprint times, the translation of the center of mass (CoM) and joint angles were obtained using three-dimensional motion analysis. 5 m STs of the CS were faster compared to the GS and PS for both directions. A detailed distance-time analysis revealed that for shorter distances only the JS was faster than the GS. Regarding the sequence in which the maximum angular velocities (max. ) in the hip, the knee, and the ankle were reached during the push off, there was a proximal-to-distal sequence for the JS and the CS, but a distal-to proximal sequence for the GS and the PS. The results reveal that the JS and the CS are superior for accelerations towards the lateral direction. Specifically, they indicate that the JS is more suitable for covering very short distances and the CS is superior for covering further distances. In addition, the distal-to-proximal sequence of max. during the push-off in the GS and the PS might indicate lower kinematic efficiency.